Conceitos de diversidade, equidade e inclusão uma proposta para implementação no âmbito de direitos humanos e empresas - Marques, Marina Dutra (2025)
The theme of this thesis is the proposition of concepts of diversity, equity, and inclusion (D.E.I.), as well as diversity, equity, and inclusion corporate programs, within the scope of business and human rights. The aim of this work is to develop substantiated, yet practical concepts for understanding and execution D.E.I. in the business environment. To this end, sociological, historical, systematic, and hermeneutic methods are used. The starting point is a contextualization of the evolution of capitalism and the behavior of the financial market, as well as of social movements, in relation to the topic under analysis as of 2020. Then, we use Iris Marion Young's theoretical reference to define oppressed social groups based on her framework of the five faces of oppression. Next, we analyze the evolution of the subject of business and human rights on the international stage, as well as labor laws related to non-discrimination and D.E.I. in the Brazilian State. Finally, and based on these premises, we layout concepts of diversity, equity, inclusion, and D.E.I. corporate programs